Islam in the West - Farrar, Max. author. aut Link
XXVII, 272 p.
Keywords: This book contributes to understanding of the contemporary relationship between Muslims and the Western societies in which they live, focusing particularly on the UK. Chapters reflect on the nature of multiculturalism, as well as a wide range of specific aspects of daily life, including religious dialogue, gender, freedom of speech and politics.